Correlation of Mitotic Indices, AgNor Count, Ki-67 and Bcl-2 with Grade and Stage in Papillary Urothelial Bladder Cancer - Goyal, Surbhi; Singh, Usha Rani; Sharma, Sonal; Kaur, Navneet (Urology Journal, 2014)
Purpose: To evaluate the mutual inter-relationship of mitotic indices, argyrophilic nuclear organizer regions (AgNOR) count, Ki-67 and B-cell lymphoma 2 protein (bcl-2) in papillary urothelial bladder cancer (pUBC), and their correlation with grade and stage. To establish the cut-off values of these markers to detect high grade and muscle invasive bladder cancer. Materials and Methods: Fifty-four patients with primary pUBC who underwent transurethral resection / radical cystectomy were analyzed retrospectively. Cell proliferation was assessed by Ki-67 labelling index, mean AgNOR count, mitotic count, mitotic activity index and mitosis/ volume index. Immunohistochemistry was done to see bcl-2 and Ki-67 expression. Correlation of these indices with tumor grade and stage and amongst themselves was assessed. The receiver operating characteristic (ROC) curves were drawn to establish the cut-off values. Results: We found a strong positive correlation of mitotic indices and Ki-67 with tumor grade (P = .000), stage (P < .05) and bcl-2 (P = .000). AgNOR count correlated positively with the grade (P = .006), mitotic indices and Ki-67 (P = .032) but not with tumor stage and bcl-2. Cytoplasmic bcl-2 immunopositivity was seen in 42.3% of low grade pUBC and 85.7% of high grade pUBC cases (P = .001). bcl-2 positivity was seen in 85% of muscle invasive pUBC as compared to only 52.9% of superficial cases. Ki-67 ≥ 32.5%, ≥ 14 mitoses/10 high power fields (hpf), ≥ 11.20 mitoses/mm2, ≥ 0.75 mitoses/100 tumor cells and AgNOR ≥ 11.55 are 100% specific for high grade bladder carcinoma. Ki-67 ≥ 59% and mitoses ≥ 36.50 per 10 hpf can indicate muscle invasion with 100% specificity. Conclusion: Cut-off values for Ki-67, mitotic indices and AgNOR can confirm high grade bladder carcinoma in equivocal cases. Ki-67 and mitotic count can serve as potential and reliable indicators of muscle invasion.